Logistic Red Flags in Mass-Casualty Incidents and Disasters: A Problem-Based Approach. Issue 2 (3rd April 2022) - Gamberini, Lorenzo; Imbriaco, Guglielmo; Ingrassia, Pier Luigi; Mazzoli, Carlo Alberto; Badiali, Stefano; Colombo, Davide; Carenzo, Luca; Flauto, Alfonso; Tengattini, Marco; Merlo, Federico; Azzaretto, Massimo; Monesi, Alessandro; et al.
Abstract: Background: Mass-casualty incidents (MCIs) and disasters are characterized by a high heterogeneity of effects and may pose important logistic challenges that could hamper the emergency rescue operations. The main objective of this study was to establish the most frequent logistic challenges (red flags) observed in a series of Italian disasters with a problem-based approach and to verify if the 80-20 rule of the Pareto principle is respected. Methods: A series of 138 major events from 1944 through 2020 with a Disaster Severity Score (DSS) ≥ four and five or more victims were analyzed for the presence of twelve pre-determined red flags. A Pareto graph was built considering the most frequently observed red flags, and eventual correlations between the number of red flags and the components of the DSS were investigated. Results: Eight out of twelve red flags covered 80% of the events, therefore not respecting the 80-20 rule; the number of red flags showed a low positive correlation with most of the components of the DSS score. The Pareto analysis showed that potential hazards, casualty nest area > 2.5km 2, number of victims over 50, evacuation noria over 20km, number of nests > five, need for extrication, complex access to victims, and complex nest development were the most frequently observed red flags. Conclusions: Logistic problems observed in MCIs and disaster scenarios do not follow the 80-20 Pareto rule; this demands for careful and early evaluation of different logistic red flags to appropriately tailor the rescue response.